Life-term imprisonment from young adulthood: a longitudinal follow-up study, 2020-2023 - Crewe, Ben (UK Data Service, 2024)
Due to a hardening of penal sensibilities and more stringent sentencing practices (mainly as a result of the 2003 Criminal Justice Act), a growing number of prisoners are serving extremely long life sentences from an early age. The UK has more life-sentenced prisoners per 100,000 of population than any other country in Europe (including Russia), and a higher proportion of life sentenced prisoners within its total sentenced prison population (10%) than any other European country or the US. The average minimum sentence length for mandatory life sentences has risen significantly in recent years. By the end of December 2018, there were 3,624 prisoners serving life sentences with tariffs of 10-20 years, and 1,862 with tariffs of more than twenty years (Ministry of Justice, 2019). These prisoners have to endure and adapt to periods inside prison that are often longer than their lives as free citizens, while maturing into adulthood in an environment that does not allow, or is hardly conducive to, normal adult experiences. Following on from an earlier study of long-term imprisonment (grant: ES/J007935/1), undertaken from 2011-2014, this research constituted an unprecedented opportunity to enhance our understanding of the dynamics and effects of long-term confinement. Its primary aims were, first, to meet Kazemian and Travis's (2015) call for longitudinal insight into the experience, dynamics and effects of long-term confinement, including the ways in which the lives, priorities and relationships of people serving life sentences change over time; second, to focus more closely on some of the key themes and findings from our original study, in particular, the ways in which individuals engage reflexively with their sentence, their index offence and their sense of self; and, third, to explore the concept of the 'depth of imprisonment' - put simply, the relationship and polarity between the prison and the outside world - that is of particular relevance for this group of prisoners. Interviews were undertaken, and surveys re-administered, with as many of our original sample as possible. Overall, this amounted to 120 of 146 initial participants, 100 in prison (out of 110 still in custody when fieldwork began) and 20 (out of 29) who had been released into the community on life licence. The research offers insight into the nature and impact of long-term imprisonment, at a time when practitioners, pressure groups and policymakers are particularly interested in the custodial and post-custodial experiences of this expanding group. It contributes significantly to a sparse and outdated research literature on the experiences of life-sentenced prisoners, serving extremely long sentences. In doing so, it addresses fundamental questions about identity, coping and humanity under intense duress, and about the lived outcomes of the most extreme form of state punishment. Due to a hardening of penal sensibilities and more stringent sentencing practices (mainly as a result of the 2003 Criminal Justice Act), a growing number of prisoners are serving extremely long sentences from an early age. The UK has more life-sentenced prisoners per 100,000 of population than any other country in Europe (including Russia), and a higher proportion of life sentenced prisoners within its total sentenced prison population (10%) than any other European country or the US. The average minimum sentence length for mandatory life sentences has risen significantly in recent years. By the end of December 2018, there were 3,624 prisoners serving life sentences with tariffs of 10-20 years, and 1,862 with tariffs of more than twenty years (Ministry of Justice, 2019). These prisoners have to endure and adapt to periods inside prison that are often longer than their lives as free citizens, while maturing into adulthood in an environment that does not allow, or is hardly conducive to, normal adult experiences. Following on from an earlier study of long-term imprisonment (grant: ES/J007935/1), undertaken from 2011-2014, this research constituted an unprecedented opportunity to very significantly enhance our understanding of the dynamics and effects of long-term confinement. Its primary aims were, first, to meet Kazemian and Travis's (2015) call for longitudinal insight into the experience, dynamics and effects of long-term confinement, including the ways in which the lives, priorities and relationships of people serving life sentences change over time; second, to focus more closely on some of the key themes and findings from our original study, in particular, the ways in which individuals engage reflexively with their sentence, their index offence and their sense of self; and, third, to explore the concept of the 'depth of imprisonment' - put simply, the relationship and polarity between the prison and the outside world - that is of particular relevance for this group of prisoners. Interviews were undertaken, and surveys re-administered, with as many of our original sample as possible. Overall, this amounted to 120 of 146 initial participants, 100 in prison (out of 110 still in custody when fieldwork began) and 20 (out of 29) who had been released into the community on life licence. The research offers insight into the nature and impact of long-term imprisonment, at a time when practitioners, pressure groups and policymakers are particularly interested in the custodial and post-custodial experiences of this expanding group. It contributes significantly to a sparse and outdated research literature on the experiences of life-sentenced prisoners, serving extremely long sentences. In doing so, it addresses fundamental questions about identity, coping and humanity under intense duress, and about the lived outcomes of the most extreme form of state punishment.